2011
DOI: 10.1016/j.neuron.2011.06.038
|View full text |Cite
|
Sign up to set email alerts
|

DEG/ENaC but Not TRP Channels Are the Major Mechanoelectrical Transduction Channels in a C. elegans Nociceptor

Abstract: Summary Many nociceptors detect mechanical cues, but the ion channels responsible for mechanotransduction in these sensory neurons remain obscure. Using in vivo recordings and genetic dissection, we identified the DEG/ENaC protein, DEG-1, as the major mechanotransduction channel in ASH, a polymodal nociceptor in Caenorhabditis elegans. But, DEG-1 is not the only mechanotransduction channel in ASH: loss of deg-1 revealed a minor current whose properties differ from those expected of DEG/ENaC channels. This curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
139
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(145 citation statements)
references
References 63 publications
5
139
1
Order By: Relevance
“…In four classes, including the touch receptor neurons (TRNs), such currents are sodium dependent and amiloride sensitive. Genetic dissection links these MeT currents to DEG/ENaC (degenerin/epithelial sodium channel) proteins in the TRNs (9-13) and a ciliated nociceptor (14)(15)(16). A transient receptor potential protein performs the role in a fifth class of mechanoreceptor that functions as a texture sensor (9,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…In four classes, including the touch receptor neurons (TRNs), such currents are sodium dependent and amiloride sensitive. Genetic dissection links these MeT currents to DEG/ENaC (degenerin/epithelial sodium channel) proteins in the TRNs (9-13) and a ciliated nociceptor (14)(15)(16). A transient receptor potential protein performs the role in a fifth class of mechanoreceptor that functions as a texture sensor (9,(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…A recent study using the nematode model has shed some light on the topic (17). Geffeney et al (17) elegantly demonstrated that worms with mutations in a degenerin gene (DEG-1) or a TRP gene (TRPV) lack the integrated behavioral responses to stimulation. However, worms with the TRPV mutation have normal mechanoreceptor currents and potential, whereas DEG-1 mutant worms do not.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms underlying proprioceptive transduction have just begun to be elucidated. Among mechanosensitive ion channel candidates such as certain members of the transient receptor potential (TRP) channels (12)(13)(14), degenerin/epithelial sodium channels (DEG/ENaC) (15)(16)(17), Piezo (18)(19)(20), transmembrane channel-like (TMC) (21), K2P (22)(23)(24), and MscL (large-conductance mechanosensitive channel) (24,25), TRPN and DEG/ENaC ion channels have been proposed to be mechanosensitive ion channels involved in proprioception in nematodes (26,27), fruit flies (6,9,10) and zebrafish (28). Recently, it was reported that Piezo2 is essential for the mechanosensitivity of mammalian proprioceptors (29).…”
mentioning
confidence: 99%